Isolation and molecular characterization of Fowl adenovirus strains in Black grouse: First reported case in Poland - Niczyporuk, Jowita Samanta (PLoS One, 2020)
This article describes the isolation, molecular characterization, and genotyping of two fowl adenovirus (FAdVs) strains with GenBank Accession numbers (MT478054, JSN-G033-18-L and MT478055, JSN-G033-18-B) obtained from the internal organs of black grouse (Lyrurus tetrix). This study also reveals the first confirmation of fowl adenovirus in Poland, supporting one of the hypotheses about the probability of fowl adenovirus interspecies transmission. The adenovirus strain sequences were investigated via phylogenetic analysis and were found to have an overall mean pairwise distance of 2.189. The heterogeneity, Relative Synonymous Codon Usage (RSCU), codon composition, and nucleotide frequencies were examined. Statistical analyses and Tajima’s test for the examined sequences were carried out. The Maximum Likelihood for the examined sequences substitutions was performed. The results of the sequence analysis identified MT478054, JSN-G033-18-L and MT478055, JSN-G033-18-B as strains of fowl adenovirus 2/11/D, with the Fowl adenovirus D complete sequence showing a 93% match. Wild birds may act as a natural reservoir for FAdVs and likely play an important role in the spreading of these viruses in the environment. The findings reported here suggest horizontal transmission within and between avian species.